Madeline Damario: capstone - Damario, Madeline, artist (Colorado State University. Libraries, 2024)
The artist's statement: I create electronic art that focuses on experimentation. I work with video editing software, creative coding, and animation software to experiment with creating interesting visuals. I am strongly interested in color, texture, and movement which I experiment with in my pieces. I am interested in using natural materials as well as completely computer-generated textures, to create different dynamics in my work. I enjoy creating fully computer-generated visuals due to imperfections that can only be created through glitches or bugged coding. I find that natural or organic source materials can have imperfections but nature in itself is dynamic and has synchronicity which is only found in natural environments. I am currently working on visuals for live music production. I am focusing on creating visuals that give the viewer a feeling of escapism and euphoria. I want to create visually stimulating video art, which makes the viewer feel good about viewing the artwork.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: electronic art